유채박을 이용한 단판적층재용 접착제의 개발 및 성능평가 - 양인; In Yang; 한규성; Gyu Seong Han; 최인규; In Gyu Choi; 김용현; Yong Hyun Kim; 안세희; Sye Hee Ahn; 오세창; Sei Chang Oh (목재공학, 2011)
목질계 판상재료 생산을 위하여 현재 주로 사용되고 있는 석유화학계 접착제는 원유의 가격 상승과 포름알데히드 방산과 같은 문제로 인해 대체 접착제에 대한 개발 필요성이 오래전부터 대두되었다. 본 연구에서는 석유 화학계 접착제를 대체하기 위하여 바이오 디젤 부산물인 유채박의 효소 가수분해를 통해 접착제를 조제하고. 이 접착제를 단판적층재 제조에 적용한 후 물리 및 기계적 특상을 조사하여 유채박의 단판적층재 제조용 접착제제조를 위한 원료화 가능성을 확인하고자 수행하였다. 먼저 유채박 접착제 조제를 위하여 유채박을 4가지 효소의 조합을 통해 개량한 다음. phenol formaldehyde (PF) prepolymer와 혼합하여 접착제를 제조하고 이를 단판적층재 제조에 사용하였다. 제조된 단판적층재의 평균함수율과 내수성은 모두 KS의 기준을 만족시키는 것으로 나타났으며, 유채박 접착제의 열분석에서 pectinase 가수분해물로 조제한 접착제를 제외하고 페놀수지 접착제와 열경화 특성이 큰 차이를 보이지 않았다. 단판적층재의 휨강도는 페놀수지 접착제로 제조한 단판적충재보다 높거나 유사한 것으로 나타나 기존 석유화학계 접착제의 대체 접착제로써 가능성을 보여주었다. 추후 접착성능의 향상을 위해 적절한 유채박의 효소가수분해 조건에 대한 연구와 도포성능 개선에 대한 연구가 필요할 것으로 생각된다. Due to the increase of oil price and the environmental issue such as the emission of volatile organic compounds, the necessity for developing alternative resins of petroleum-based adhesive resins, which have extensively been used for the manufacture of wood-based products, has been speculation since the early 1990. In our study, rapeseed flour (RSF), which is the by-product of bio-diesel produced from rapeseed, were hydrolyzed by enzymes As a crosslinking agents of the RSF hydrolyzates, phenol-formaldehyde prepolymers (PF) were prepared. The RSF hydrolyzates and PF were mixed to complete the formulation of RSF-based adhesive resins, and the resins were applied to make the laminated veneer lumber (LVL). The physical and mechanical properties of the LVL were measured to examine whether RSF can be used as raw materials of adhesive resins for the fabrication of LVL or not. The average moisture content and soaking delamination rate of the LVL bonded with RSF-based adhesive resins exceeded the minimum requirement of KS standard. Moreover, thermal analysis of the RSF-based resins showed similar tendencies except for the RSF-based adhesive resins formulated with pectinase-hydrolyzed RSF. The bending strengths of the LVI. were higher than that of the LVL made with commercial PF resins These results showed the potential of RSF as a raw material of alternative adhesives for the production of LVL Further works on the optimal conditions of RSF hydrolysis and spreading characteristics for RSF-hased adhesive resins is required to improve the adhesive performance of RSF-based resins